Catastrophic Health Care Expenditure among Older People with Chronic Diseases in 15 European Countries. - Jelena Arsenijevic; Milena Pavlova; Bernd Rechel; Wim Groot (PLoS ONE, 2016)
INTRODUCTION:It is well-known that the prevalence of chronic diseases is high among older people, especially those who are poor. Moreover, chronic diseases can result in catastrophic health expenditure. The relationship between chronic diseases and their financial burden on households is thus double-sided, as financial difficulties can give rise to, and result from, chronic diseases. Our aim was to examine the levels of catastrophic health expenditure imposed by private out-of-pocket payments among older people diagnosed with diabetes mellitus, cardiovascular diseases and cancer in 15 European countries. METHODS:The SHARE dataset for individuals aged 50+ and their households, collected in 2010-2012 was used. The total number of participants included in this study was N = 51,661. The sample consisted of 43.8% male and 56.2% female participants. The average age was 67 years. We applied an instrumental variable approach for binary instrumented variables known as a treatment-effect model. RESULTS:We found that being diagnosed with diabetes mellitus and cardiovascular diseases was associated with catastrophic health expenditure among older people even in comparatively wealthy countries with developed risk-pooling mechanisms. When compared to the Netherlands (the country with the lowest share of out-of-pocket payments as a percentage of total health expenditure in our study), older people diagnosed with diabetes mellitus in Portugal, Poland, Denmark, Italy, Switzerland, Belgium, the Czech Republic and Hungary were more likely to experience catastrophic health expenditure. Similar results were observed for diagnosed cardiovascular diseases. In contrast, cancer was not associated with catastrophic health expenditure. DISCUSSION:Our study shows that older people with diagnosed chronic diseases face catastrophic health expenditure even in some of the wealthiest countries in Europe. The effect differs across chronic diseases and countries. This may be due to different socio-economic contexts, but also due to the specific characteristics of the different health systems. In view of the ageing of European populations, it will be crucial to strengthen the mechanisms for financial protection for older people with chronic diseases.